Autologous Ear Reconstruction - Olshinka, Asaf; Louis, Matthew; Truong, Tuan A. (Seminars in Plastic Surgery, 2017)
Since the pioneering use of autologous rib cartilage for the reconstruction of microtia, there have been significant advances in surgical technique that have helped to ameliorate the psychological burden of microtia. To date, the use of rib cartilage for auricular reconstruction is one of the most enduring and ubiquitous techniques for microtia reconstruction as it provides excellent aesthetic results with lasting durability. In this review, the authors outline the most common methods of microtia reconstruction with a comparison of each technique and illustrative case examples.
Keywords: Brent; Nagata; autologous ear reconstruction; Tanzer; cartilage